The Effect of Silver Nanoparticles on Callus Induction and Contamination Control in Tissue Culture of Date Palm (Phoenix dactylifera L.) cv. Sayer - Salih, Ansam M.; AL-Aradi, Haleemah J.; Farhoud, Aseel A. (Basrah Journal Of Date Palm Research, 2024)
Plant tissue culture provides an important option for multiplying plants and improving their production within a limited period of time. Attention is drawn to ways to develop this technology and raise its performance level by involving other technologies such as nanotechnology. The case study was conducted in the tissue culture laboratory of the Date palm Research Centre at the University of Basrah to determine the biological effects of silver nanoparticles in combating pollution associated with tissue culture of date palms of the Sayer cultivar. The apical buds were grown in MS medium. Supplemented with plant growth regulators and AgNPs concentrations (1, 2, 3, 4, and 5) mg.L-1 in addition to the control treatment free of AgNPs, The highest percentage of callus induction and the lowest percentage of contamination were indicated in the date palm tissue culture establishment stage, reaching 100% and 10%, respectively, in the 1 mg.L-1 treatment. The same treatment also recorded the highest average number of embryos, reaching 19.2 embryos. The highest average fresh and dry weight of callus reached 1.846 and 1.50 respectively, while the highest average number of embryos reached in treatments 1, 2 and 3 nano silver, with a significant difference from the other treatments. The values of these indicators decreased with the increase in the concentration of silver nanoparticles.